SPSSI Research Summary on Media Violence. Issue 1 (4th November 2015) - Anderson, Craig A.; Bushman, Brad J.; Donnerstein, Edward; Hummer, Tom A.; Warburton, Wayne
Abstract : Media use among children has increased sharply in recent years, due, in part, to a significant increase in multimedia portable devices. On average, U.S. children aged 8–18 spend more than 7 hours a day engaging with media. Governments, professional bodies, and citizens have become increasingly concerned about the social and personal impact of media with violent themes and depictions. This has been driven, in part, by a series of tragic mass killings in which it appears that media violence exposure may have been a contributing risk factor. Public health and child development professionals are increasingly convinced by converging scientific findings linking media violence exposure to increased aggression. Hundreds of scientific studies involving hundreds of thousands of participants and a wide range of empirical methods have investigated the effects of exposure to violent media. The studies show that: In experimental studies, even brief exposure to media can cause desensitization to real‐world violence, increases in aggressive thoughts, feelings, and behaviors, and decreases in empathy and helping behavior. Short‐term effects of media violence and basic psychological processes produce cumulative effects over time, as explained by well‐established theories and research and social, developmental, and cognitive processes. Indeed, habitual exposure to media violence produces relatively stable changes in personality traits, such as trait aggression. Longitudinal research—studies that follow individuals over time—rule out plausible alternate explanations to these findings (for example, that the association between media violence and aggressive behavior is entirely the result of inherently aggressive people chasing more violent media). Media violence exposure is linked with physically hurting others, using words to hurt others, and deliberately damaging the relationships of others. Links have been found between violent media exposure and "real‐world" violent behaviors such as assault, intimate partner violence, robbery, and gang fighting. A growing body of evidence suggests that media with helping and presocial messages can lead to increases in empathy and helping behaviors, and decreases in aggressive behaviors. Changing a child's media diet from aggressive/violent to presocial, educational, and age‐appropriate can reduce aggression, increase presocial behavior, and improve educational outcomes. There is some consensus that a moderate amount of recreational screen time for school children is 1–2 hours per day, and that when screen media are coviewed by and discussed with parents and teachers, children are somewhat less harmed by violent media. Media violence is only one of many risk factors for aggression, but it is one that policy makers, professionals, and parents can address at little cost. Policy makers and media producers would benefit from working cooperatively with media psychologists who have backgrounds in social, developmental, cognitive, and/or personality psychology to produce evidence‐informed policies and media products. Policy makers should consider: (1) revising classification systems to be both evidence‐based and parent‐friendly, (2) including carefully constructed media literacy content in school curricula, and (3) creating a public education campaign on the impact of media violence.